CMC-coated Fe3O4nanoparticles as new MRI probes for hepatocellular carcinoma - Sudarat Sitthichai (2018)
© 2015 Elsevier B.V. All rights reserved. Pure Fe3O4nanoparticles and Fe3O4magnetic nanoparticles (MNPs) coated with carboxymethyl cellulose (CMC) were successfully prepared by co-precipitating of FeCl2·4H2O and FeCl3·6H2O in the solutions containing ammonia at 80 °C for 3 h. Phase, morphology, particle-sized distribution, surface chemistry, and weight loss were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) including high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED), thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy. In this research, CMC-coated Fe3O4MNPs consisting of Fe2+and Fe3+ions with 543.3-mM-1s-1high relaxivity were detected and were able to be used for magnetic resonance imaging (MRI) application with very good contrast for targeting hepatocellular carcinoma (HCC) without any further vectorization.